Performance of a SARS-CoV-2 antigen rapid immunoassay in patients admitted to the emergency department. (September 2021) - Leli, Christian; Di Matteo, Luigi; Gotta, Franca; Cornaglia, Elisa; Vay, Daria; Megna, Iacopo; Pensato, Rosalia Emanuela; Boverio, Riccardo; Rocchetti, Andrea
Highlights: RT-PCR is the gold standard for SARS-CoV-2 detection, but the results take time to appear Rapid antigen tests are spreading, with extreme variability in diagnostic accuracy The microfluidic antigen test showed excellent performance compared with the molecular one A combination of the two tests improved the overall diagnostic capability Abstract: Objectives: Given the ongoing pandemic emergency, there is a need to identify SARS CoV-2 infection in various community settings. Rapid antigen testing is spreading worldwide, but diagnostic accuracy is extremely variable. Our study compared a microfluidic rapid antigen test with a reference molecular assay in patients admitted to the emergency department (ED) of a general hospital from October 2020 to January 2021. Methods: Nasopharyngeal swabs collected in patients with suspected COVID-19 and in patients with no symptoms suggesting COVID-19, but requiring hospitalization, were obtained. Results: 792 patients of median age 71 years were included. With a prevalence of 21%, the results showed: 68.7% (95% confidence interval [CI]: 60.9–75.5) sensitivity; 95.2% (95% CI: 93.1–96.7) specificity; 79.2% (95% CI: 71.4–85.3) positive predictive value (PPV); 91.9% (95% CI: 89.5–93.9) negative predictive value; 3.8 (95% CI: 2.7–5.3) positive likelihood ratio (LR+); and 0.09 (95% CI: 0.07–0.1) negative likelihood ratio (LR−). In the symptomatic subgroup, sensitivity increased to 81% (95% CI: 70.3–88.6) and PPV to 96.9% (95% CI: 88.5–99.5), along with an LR+ of 32 (95% CI: 8.2–125.4). Conclusions: The new rapid antigen test showed an overall excellent diagnostic performance in a challenging situation, such as that of an ED during the COVID-19 emergency.